Analysis of Gross Tonnage (GT) Capacity Installed On Traditional Wooden Ships In Penajam Paser Utara - Manik, Aljoiden; Arifuddin, Andi Mursid Nugraha; Pawara, Muhammad Uswah; Nurcholik, Samsu Dlukha; Ikhwani, Rodlian Jamal (Indonesian Journal of Maritime Technology, 2023)
To identify the GT of traditional wooden boats built at PPU, an investigation of the GT on the boat is carried out. The GT of the North Penajam Paser traditional wooden ship was identified using domestic regulations issued by the government through the Ministry of Transportation, PM No. 45 of 2021 and PP No. 85 of 2021 concerning PNBP of the Directorate General of Sea Transportation. Before being operated, every ship must be measured to determine the length, width, depth and tonnage of the ship in accordance with the ship measurement method. According to Law number 20 of 1997, "Non-Tax State Revenue (PNBP) is all Central Government revenue that does not come from revenues taxation". ship data studied for determining gross tonnage, Lpp: 17.76m, LoA: 21.90 m, Lwl: 19.06m, B: 4m, H: 2m, T: 1.40m, Cb: 0.50. Calculating ship tonnage or calculating gross tonnage and net tonnage has two methods, namely the empirical method and the analytical method. The analytical ship GT value is 14.16 and the empirical ship GT is 14.79. The total amount of PNPB on ships based on analytics is IDR 5,600,704.74. The total empirical PNPB amount is IDR 8,43,031.01. The difference between analytical and empirical PNBP is IDR 242,327.01. The difference between GT based on analytical and GT empirical methods is 0.63. the comparison level between the two methods is 4%.